2003
DOI: 10.1507/endocrj.50.643
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Dependent Insulinotropic Polypeptide Induced Growth Hormone Secretion in Acromegaly

Abstract: Abstract. Glucose-dependent insulinotropic polypeptide (GIP), a peptide released from the intestines after meals, is thought to stimulate insulin secretion. GIP receptor cDNA has recently been cloned and its mRNA has been recognized in several organs including the pituitary, but the physiological roles of GIP receptors of the pituitary have yet to be determined. We have demonstrated the possibility that GIP stimulates GH secretions from the pituitary adenoma cells of acromegalics. GIP-stimulated GH responses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 32 publications
4
14
0
Order By: Relevance
“…Similar results were seen with the use of GHRH antagonist MZ-4-71 and LHRH antagonist Cetrorelix (132). In acromegaly the presence of ectopic TRH, GnRH or GIP receptors explains the frequently observed paradoxical increase in GH after administration of TRH, GnRH or oral glucose respectively (133,134,135,136,137,138). GIPR expression was investigated in 43 somatotropinomas and 12 normal pituitary glands by quantitative RT-PCR, western blotting and immunohistochemistry.…”
Section: European Journal Of Endocrinologysupporting
confidence: 54%
“…Similar results were seen with the use of GHRH antagonist MZ-4-71 and LHRH antagonist Cetrorelix (132). In acromegaly the presence of ectopic TRH, GnRH or GIP receptors explains the frequently observed paradoxical increase in GH after administration of TRH, GnRH or oral glucose respectively (133,134,135,136,137,138). GIPR expression was investigated in 43 somatotropinomas and 12 normal pituitary glands by quantitative RT-PCR, western blotting and immunohistochemistry.…”
Section: European Journal Of Endocrinologysupporting
confidence: 54%
“…Indeed, acromegalic patients exhibiting paradoxical GH responses to oral glucose load increased their plasma GH levels in response to intravenous GIP stimulation. Furthermore, loss of this paradoxical GH response when glucose was administered intravenously supported the hypothesis of the implication of a gastrointestinal hormone [102]. In addition, GIP stimulation of GIPR-expressing somatotroph adenomas in primary culture increased GH release in 80% of these adenomas, with 60% reaching statistical significance [103].…”
Section: Ogtt In the Diagnosis Of Acromegalymentioning
confidence: 91%
“…An altered interplay between somatostatin and GHRH has been suggested [98] but not well documented. Recently, in analogy to food-dependent Cushing’s syndrome [99-101], a role for ectopic expression of the glucose-dependent insulinotropic polypeptide receptor ( GIPR ) in somatotroph adenomas for mediating the paradoxical GH response to OGTT has been evoked [88, 102]. We have recently shown that among 41 pituitary adenomas, all 10 samples from patients with paradoxical GH responses displayed ectopic GIPR expression [96].…”
Section: Ogtt In the Diagnosis Of Acromegalymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the demonstrated role of cAMP in somatotroph proliferation and GH secretion, in the present study, we aimed to identify the novel factors that might alter the cAMP pathway and potentially be involved in the pathogenesis of acromegaly. A possible role of GIPR in mediating paradoxical increase of GH after OGTT in acromegalic patients had already been suggested (19); therefore, we decided to investigate the expression of such receptor in GH‐secreting pituitary adenomas and in normal pituitary glands, taking into account the GNAS1 mutational status in the former. In addition, we evaluated the effects of GIP on regulating cAMP levels and GH transcription in the pituitary lactosomatotrophic GH3 cell line transfected with GIPR .…”
mentioning
confidence: 99%